2020
DOI: 10.1371/journal.pone.0243098
|View full text |Cite
|
Sign up to set email alerts
|

Hypergravity as a gravitational therapy mitigates the effects of knee osteoarthritis on the musculoskeletal system in a murine model

Abstract: Insights into the effects of osteoarthritis (OA) and physical interventions on the musculoskeletal system are limited. Our goal was to analyze musculoskeletal changes in OA mice and test the efficacy of 8-week exposure to hypergravity, as a replacement of physical activity. 16-week-old male (C57BL/6J) mice allocated to sham control and OA groups not centrifuged (Ctrl 1g and OA 1g, respectively) or centrifuged at 2g acceleration (Ctrl 2g and OA 2g). OA 1g displayed decreased trabecular bone in the proximal tibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Thus, combining drug administration with hypergravity exposure could potentially be a strategy to improve drug efficacy. It has also been shown that hypergravity has positive effects on trabecular bone and muscle typology in osteoarthritic mice [ 103 ]. These effects were similar to those induced by resistance exercises, but negative effects were noted for cortical bone.…”
Section: How Can Gepam Contribute To the Identification Of Countermentioning
confidence: 99%
“…Thus, combining drug administration with hypergravity exposure could potentially be a strategy to improve drug efficacy. It has also been shown that hypergravity has positive effects on trabecular bone and muscle typology in osteoarthritic mice [ 103 ]. These effects were similar to those induced by resistance exercises, but negative effects were noted for cortical bone.…”
Section: How Can Gepam Contribute To the Identification Of Countermentioning
confidence: 99%
“…Exposure to spaceflight conditions could result in physical and physiological stress due to gravitational alterations [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. The greatest gravitational change that living organisms experience during escape and re-entry into the Earth’s atmosphere is the high gravity applied during the ascent of the launch vehicle and the rapid change to weightlessness experienced thereafter.…”
Section: Introductionmentioning
confidence: 99%